The Relationship Between Financial Development and the Composite Stock Price Index in Emerging Market Countries: A Panel Data Evidence - Hidayat, Ariodillah; Liliana,; Harunurrasyid,; Shodrokova, Xenaneira (Organizations and Markets in Emerging Economies, 2023)
This study examines the influence of financial development variables on the Composite Stock Price Index (CSPI) in Emerging Market Countries. This study uses secondary data obtained from the International Monetary Fund and Yahoo Finance, with an annual data period of 2000–2020. Panel data regression analysis using the random effects model was performed to analyze data. The results showed that Financial Market Access Index (FMAI) and Financial Market Depth Index (FMDI) variables had a positive and significant relationship affecting CSPI, while Financial Market Efficiency Index (FMEI) had a negative and significant relationship to CSPI. The FMEI results negatively affecting CSPI indicate the need for improvements in financial market efficiency. Increased efficiency can help ensure that relevant and accurate information is available quickly and fairly to all parties, driving better investment decisions.
Keywords: Financial Development; Composite Stock Price Index; emerging market